2007
DOI: 10.1111/j.1600-079x.2007.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin reduces the neuronal loss, downregulation of dopamine transporter, and upregulation of D2 receptor in rotenone‐induced parkinsonian rats

Abstract: Parkinson's disease (PD) is a movement disorder resulting from nigrostriatal dopaminergic neurodegeneration. The impairment of mitochondrial function and dopamine synaptic transmission are involved in the pathogenesis of PD. Two mitochondrial inhibitors, 1-methyl-4-phenylpyridine (MPP(+)) and rotenone, have been used to induce dopaminergic neuronal death both in in vitro and in vivo models of PD. Because the uptake of MPP(+) is mediated by the dopamine transporter (DAT), we used a cell-permeable rotenone-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 55 publications
3
41
0
Order By: Relevance
“…The authors also measured higher activity of SOD and catalase in the brain when melatonin was administered. These results were supported by another rotenone study in which rats chronically exposed to rotenone were protected by co-treatment with melatonin [115]. In the same year, Capitelli et al, [98] conducted an MPTP test in rats.…”
Section: Melatonin (Supplementary Materials Table A1)supporting
confidence: 67%
“…The authors also measured higher activity of SOD and catalase in the brain when melatonin was administered. These results were supported by another rotenone study in which rats chronically exposed to rotenone were protected by co-treatment with melatonin [115]. In the same year, Capitelli et al, [98] conducted an MPTP test in rats.…”
Section: Melatonin (Supplementary Materials Table A1)supporting
confidence: 67%
“…Several studies demonstrated melatonin treatment prevents dopamine-producing neuronal loss and dopamine transporter down-regulation in a rotenone model of PD [40]. Hendaus et al demonstrated that melatonin plays a role in neuroprotection in a phenylhydrazine hydrochloride (PHZ)-induced perinatal hypoxic-ishcemic encephalopathy model in rats.…”
Section: Effect Of Melatonin On Hypersomnolencementioning
confidence: 99%
“…Melatonin prevents the nigrostriatal neurodegeneration and alpha-synuclein aggregation [72] induced by rotenone. Melatonin scavenges rotenone-induced hydroxyl radicals and restores the decreased glutathione level and changes in the catalytic activities of superoxide and catalase in the substantia nigra [74].…”
Section: Melatonin and Rotenonementioning
confidence: 98%
“…Rotenone leads to the dopaminergic neurodegeneration and reduces the number of TH-positive neurons of the nigrostriatal pathway. Although degeneration caused by rotenone is non-specific in nature, it is the only neurotoxin which exhibits well-defined Lewy body formation and aggregation of alpha-synuclein along with depletion of glutathione, disruption of axonal transport, and onset of several critical histological, biochemical, and pathological hallmarks of sporadic PD [23,27,72]. Since rotenone does not rely on the dopamine transporter uptake to exert neurotoxicity, therefore, it could be considered as an ideal model to assess neuroprotection [73].…”
Section: Melatonin and Rotenonementioning
confidence: 98%
See 1 more Smart Citation